Over a million students use our free study notes to help them with their homework
To solve this we must use the chain rule which is dy/dt * dt/dx. Firstly, we differentiate dy/dt. For this we must use the quotient rule, this gives us dy/dt=(9te^3t - 3e^3t)/9t^2. Now for dx/dt, by subst...
You can not integrate tan2x but you can integrate sec2x Since sec2x = 1 + tan2x Then tan2Answered by Nandini P. • Maths tutor19755 Views
To start with, try and spot whether or not two of the coeffecients (numbers next to the letters) are the same for either question (i.e. could be a 3x in one equation and a 3x in the other). This also work...
Unit circle: x2 + y2 = 1 when x = sqrt(3)/2: y2 = 1 - (sqrt(3)/2)2 y2 = 1 - 3/4 y2 = 1/4 y = 1/2 or -1/2 (first quadrant, so y is posi...
Set f(x)= (x^4)-14x. f’(x)=4(x^3)-14=2(2(x^3)-7). Thus we can write (2(x^3)-7)/((x^4)-14x)=(1/2)f’(x)/f(x). The integral of f’(x)/f(x)=ln|f(x)|+c. Thus the integral of (2(x^3)-7)/((x^4)-14x) is (1/2)(ln|f...
←
428
429
430
431
432
→
Internet Safety
Payment Security
Cyber
Essentials